Fabrication of hydrophilic and hydrophobic membranes inspired by the phenomenon of water absorption and storage of cactus - Shi, Yana; Kim, Kiwoong (Frontiers in Materials, 2022)
Water shortage has become one of the most serious practical problems facing humans. Thus, an efficient and economical water-harvesting technology is urgent to develop. In this work, to prepare samples of hydrophilic and hydrophobic bilayer structures, three kinds of hydrophobic polyethylene terephthalate (PET) fibers with different pore diameters were simply dip coated to fabricate hydrophobic surfaces, which showed different hydrophobic effects. Titanium dioxide was then sprayed onto the hydrophobic surface to form irregular protrusions and to increase surface roughness and surface energy. The distribution amount of titanium dioxide was controlled by adjusting the spraying distance of titanium dioxide. Finally, ultraviolet irradiation was performed. The light response made the protrusions superhydrophilic and improved capture mist and moisture by increasing the surface wettability and Laplace pressure. Water-collection test was performed for samples with different spraying distances irradiated by ultraviolet rays. The spraying distance with the best water-collection efficiency was achieved. The hydrophilic surface (particles) was attached onto a hydrophobic membrane, which quickly and effectively captured the mist and converted it to water, thereby easily discharging a large amount of water. This study is expected to promote the development of fogging drainage and alleviate the problem of water shortage.